Biotechnology options for improving livestock production in developing countries, with special reference to sub-Saharan Africa - Rege, J.E.O. (International Livestock Research Institute, 1996)
Techniques of modern biology such as molecular cloning of genes, gene transfer, genetic manipulation of animal and plant embryo transfer, genetic manipulation of rumen microbes, chemical and biological treatment of low quality animal feeds for improved nutritive value, genetically engineered immunodiagnostic and immunoprophylactic agents as well as veterinary vaccines, inter alia, are a reality today and are finding their ways into research and development programmes of developing countries. Biotechnology is offering unprecedented opportunities for increasing agricultural productivity and for protecting the environment through reduced use of agro-chemicals. The major thrust in biotechnology research is currently directed at solving immediate problems of industrialised countries, with major investments coming from transnational companies. However, many of the new discoveries and products will find their biggest markets in developing countries where the potential for improvement in agricultural productivity and health is greatest. The importance of biotechnology and its relevance is only slowly being accepted by policy makers in developing countries. In the presence of economic crisis, strong fiscal constraints, rapid social change and constant political instabilities, the difficulties associated with major policy changes in developing countries are enormous. This paper reviews available biotechnologies with potential application in livestock improvement and identifies those which have been or may be applied in developing countries in general, and Africa in particular. The review covers biotechnology applications in the areas of animal genetics and breeding, including conservation of animal genetic resources, animal health, physiology of lactation and growth, and animal nutrition.